Clinical Impact of Multidetector Row Computed Tomography before Bronchial Artery Embolization in Patients with Hemoptysis: A Prospective Study. Issue 1 (February 2013) - Gupta, Mudit; Srivastava, Deep Narayan; Seith, Ashu; Sharma, Sanjay; Thulkar, Sanjay; Gupta, Rashmi
Purpose: To evaluate prospectively the role and impact of multidetector row computed tomography (MDCT) before bronchial artery embolization (BAE) in patients with hemoptysis. Methods: MDCT of the thorax was performed in 27 patients (21 men, 6 women; age range, 22-70 years; mean, 39 years) with hemoptysis who were referred for BAE. Transverse, multiplanar reconstruction, and 3-dimensional reconstruction (maximum intensity projection and volume rendered) images were analysed to identify the abnormal hypertrophied bronchial and nonbronchial systemic arteries causing hemoptysis, their origin and course were noted. Digital subtraction angiography was performed with the knowledge of findings of MDCT. Selective arteriogram of abnormal bronchial as well as nonbronchial arteries was performed. Embolization was attempted in 25 of these patients (92.6%) by using polyvinyl alcohol particles (350-500 μm), Gelfoam or Embospheres (400-700 μm). Follow-up was done for a mean period of 20.5 months. Results: Based on MDCT, 2 of 27 patients were found unsuitable for BAE. On computed tomography, 38 arteries (27 bronchial and 11 nonbronchial systemic arteries) were identified as abnormal hypertrophied vessels. On angiography, 34 of these arteries (25 bronchial and 9 nonbronchial systemic arteries) were found to be responsible for hemoptysis. Three of these arteries could not be evaluated during angiography, and 1 artery that was identified as abnormal on computed tomography was found normal on angiography. All 25 bronchial and 9 nonbronchial systemic arteries that cause hemoptysis were detected at MDCT. Embolization was successful in 23 of 25 patients. Conclusion: MDCT enables detection and depiction of all bronchial and nonbronchial systemic arteries causing hemoptysis.